2021
DOI: 10.1007/s12144-020-01242-w
|View full text |Cite
|
Sign up to set email alerts
|

Stress management training and gratitude journaling in the classroom: an initial investigation in Indian context

Abstract: Stress and allied difficulties are pervasive among school students in present times. This concern is further magnified in the Indian context with the large represention of young people in the population and limited resources to match. The present study aimed to evaluate the impact of a classroom based stress management training and gratitude journaling intervention (Flinchbaugh et al., 2012) among Indian adolescents. The intervention curriculum was adapted to suit the study context. A total of 238 students (57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 73 publications
(81 reference statements)
0
12
0
Order By: Relevance
“… Unclear if interaction is significant. Khanna et al (2021) 51 238 Indian school students M age = 12.3 8-week intervention EG1: Gratitude journaling EG2: Stress management EG3: Gratitude and stress combined Control: No activity Pre/post Nonsignificant decrease in LS in gratitude condition. No relative increase versus control.…”
Section: Resultsmentioning
confidence: 99%
“… Unclear if interaction is significant. Khanna et al (2021) 51 238 Indian school students M age = 12.3 8-week intervention EG1: Gratitude journaling EG2: Stress management EG3: Gratitude and stress combined Control: No activity Pre/post Nonsignificant decrease in LS in gratitude condition. No relative increase versus control.…”
Section: Resultsmentioning
confidence: 99%
“…Five intervention studies based on life-skill-training were found to be effective in promoting self-efficacy [ 72 , 73 ], self-esteem [ 73 , 74 ], and reducing depression/anxiety-like symptoms [ 72 , 75 , 76 ]. Courses covering stress management skills have also been reported to improve life satisfaction, increase happiness and decrease anxiety levels among students in developing countries [ 77 79 ]. In practice, innovative teaching forms such as the game play [ 67 , 80 , 81 ] and outdoor learning [ 82 , 83 ] embedded in the traditional classes could help address the mental health and social participation concerns for children and youth.…”
Section: Resultsmentioning
confidence: 99%
“…The anxiety specifically related to academic achievement and test-taking at school was frequently reported among students who felt pressured and overwhelmed by the continuous evaluation of their academic performance [ 98 , 103 , 104 ]. In such high-pressure academic environments, strategies to alleviate the levels of stress among students should be incorporated into intervention efforts, such as stress management skill training [ 77 79 ], CBT-based curriculum [ 62 , 64 , 66 , 105 ], and attention training [ 106 ]. Therefore, school supportive policies that allow students continued access to various non-academic activities as well as improve their social aspect of participation may be one fruitful avenue to promote student well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Writing helps to untangle and better define underlying stressors and is itself meditative. 16,17 However, ensure that your journaling is focused on positive emotional responses and aims to determine the positive benefits within any stressful event; those solely expressing negative emotions were found to have higher levels of stress and anxiety afterward than they had before. 17…”
Section: Communicate About Stressorsmentioning
confidence: 99%